The Influence of Occupational Safety and Occupational Health On the Performance of Production Employees at AT PT. Musaya Kreasindo - Yudi Kristanto; Pupung Purnamasari (The International Journal of Education Management and Sociology, 2022)
This research is the result of a survey at PT Musaya Kreasindo which produces. The purpose of this study was to determine the effect of Occupational Safety and Health on Production Employee Performance at PT Musaya Kreasindo on 50 employees as a sample. The research method used is quantitative with associative techniques. The research objectives want about the influence between Occupational Safety on Employee Performance, the influence between Occupational Health on Employee Performance, and the influence between Occupational Safety and Health together on Employee Performance. The results showed that there was an influence between Occupational Safety and Occupational Health together on Employee Performance as indicated by the results of the multiple linear regression equation, namely Y' = 23.64 + 0.74 X1 + 0.26 X2. The results of this study are expected to contribute thoughts to PT Musaya Kreasindo to pay more attention to employee safety and health in order to improve employee performance.